Rendimientos y eficiencia en el uso del agua de lechuga y tomate cherry en jardines urbanos - Fernández, Hugo Antonio; Salazar-Moreno, Raquel; Fitz-Rodríguez, Efrén; López Cruz, Irineo.L; Schmidt, Uwe; Dannehl, Dennis (Tecnología y ciencias del agua, 2023)
Urban and peri-urban horticulture presents major challenges, such as low water and land availability for agricultural use. So far, there are no data on the amount of water needed for vegetable production in Mexico City (CDMX). Therefore, the objective of this study was to estimate the yield and water use efficiency of two representative crops in urban gardens, including romaine lettuce and cherry tomato, for 13 urban gardens in CDMX. In addition, the rainwater storage capacity was estimated using data from the closest weather station from each orchard, in order to make statements about the coverage of the water demand for the plants. Yield and water use efficiency for lettuce production ranged between 0.10 and 1.20 kg m-2 as well as 0.21 to 2.93 kg m-3 water, respectively. These indicators for the case of cherry tomato were between 0.25 and 3.40 kg m-2 and between 0.32 and 5.52 kg m-3 water, respectively. Irrigation in the urban gardens was done in an empirical way and using fresh water. It was found, in most of the cases, an excess of water supply which can be up to 0.27 and 0.4 m3 m-2 for a complete growth season of lettuce and cherry tomato. The rainwater storage capacity in a year was estimated using an 80 % probability of exceedance. The accumulated rainwater storage varies from 0.261 to 0.5215 m3 m-2 in the orchards, which could supply the water requirements for a complete season of lettuce (0.128 to 0.389 m3 m-2) or cherry tomato (0.145 to 0.569 m3 m-2).